2012
DOI: 10.4236/as.2012.38123
|View full text |Cite
|
Sign up to set email alerts
|

Decumbenones A–C from marine fungus <i>Aspergillus sulphureus</i> as stimulators of the initial stages of development of agricultural plants

Abstract: The effect of decumbenones A (1), B (2) and C (3) from the marine-derived strain of the fungus Aspergillus sulphureus on the growth of seedling roots of buckwheat, wheat, barley and corn at the concentration range 10 −5-10 −18 M was studied. It was shown that decumbenone B had a stimulatory effect on the growth of seedling roots of buckwheat, decumbenone A-on the growth of seedling roots of spring soft wheat, decumbenone Con the growth of seedling roots of spring barley, decumbenone A, B and Con the growth of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
0
4
0
4
Order By: Relevance
“…Our results agree with published data, according to which some metabolites of marine organisms stimulate root growth of seedlings. The same effects were observed for the steroid glycosides from the starfish Asteropsis carinifera [9], diterpene glycosides from Acremonium striatisporum [10], decumbenones from Aspergillus sulphureus [11], alkaloids from Aspergillus fumigatus [12], and oxirapentyn E from the marine isolate of the fungus Isaria felina [13] on the root growth of seedlings of monocotyledon and dicotyledon plants.…”
mentioning
confidence: 57%
“…Our results agree with published data, according to which some metabolites of marine organisms stimulate root growth of seedlings. The same effects were observed for the steroid glycosides from the starfish Asteropsis carinifera [9], diterpene glycosides from Acremonium striatisporum [10], decumbenones from Aspergillus sulphureus [11], alkaloids from Aspergillus fumigatus [12], and oxirapentyn E from the marine isolate of the fungus Isaria felina [13] on the root growth of seedlings of monocotyledon and dicotyledon plants.…”
mentioning
confidence: 57%
“…Future studies could also look beyond calbistrins as molecule class and investigate the mode of action and benefits for the producers of the related decumbenones which were shown to inhibit melanisation of Magnaporthe grisea [37] and stimulating the germination of agricultural plants [38]. As our study also identified a potential calbistrin cluster in the root endophyte Colletotrichum tofieldiae which supports growth of Arabidopsis thalina under low phosphate conditions [39], it might be worth to investigate the production and role of decumbenones and calbistrins in these interactions and wether they are valuable for fending off other soil-thriving fungi or promoting growth of the host plant.…”
Section: Discussionmentioning
confidence: 99%
“…Polyketides containing “decalin” moiety exhibit diverse biological properties such as anticancer, antimicrobial, neurotrophic, and growth-stimulating activity [23,24,25,26,27]. Twelve new polyketides, named zosteropenillines A–L ( 1 – 12 ), have been isolated from the extract of the marine-derived fungus Penicillium thomii .…”
Section: Discussionmentioning
confidence: 99%
“…Zosteropenillines A–L ( 1 – 12 ) belong to the series of lovastatin-related polyketides that are formed by an enzymatic intramolecular Diels–Alder cycloaddition of a linear hexaketide precursor [ 20 , 21 , 22 ]. Polyketides containing “decalin” moiety exhibit diverse biological properties such as anticancer, antimicrobial, neurotrophic, and growth-stimulating activity [ 23 , 24 , 25 , 26 , 27 ]. Twelve new polyketides, named zosteropenillines A–L ( 1 – 12 ), have been isolated from the extract of the marine-derived fungus Penicillium thomii .…”
Section: Discussionmentioning
confidence: 99%